2006
DOI: 10.1093/rheumatology/kel218
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of patients with juvenile idiopathic arthritis coming from 3 different geographic areas. The PRINTO multinational quality of life cohort study

Abstract: We found that patients with JIA have a significant impairment of their HRQL compared with healthy peers, particularly in the physical domain. Disability and pain are the most important determinants of physical and psychosocial well-being irrespective of the geographic area of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
101
5
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 16 publications
11
101
5
5
Order By: Relevance
“…In other studies, physical disability also appears to be strongly related to HRQOL (14,16,22,39). Besides, physical activity is generally impaired in adolescents with JIA (40).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…In other studies, physical disability also appears to be strongly related to HRQOL (14,16,22,39). Besides, physical activity is generally impaired in adolescents with JIA (40).…”
mentioning
confidence: 67%
“…HRQOL studies in JIA patients are scarce in Europe (14,15,23) and include heterogeneous groups of patients based on different age cohorts and with different national health care systems (19,24). Many studies use proxy reporting (14,25,26), whereas other studies have shown that self-reporting appears to be more reliable (20,27) for evaluating HRQOL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall quality of life, defined as an individual's perception of their position in life, may show little impact of a disease or its treatment, but HRQoL is expected to be responsive to therapeutic interventions (3)(4)(5)(6)(7)(8). Suboptimal HRQoL in children with juvenile idiopathic arthritis (JIA) has been reported up to 6 years after diagnosis (6,(9)(10)(11)(12)(13), and recent studies suggest a dissociation between HRQoL and disease activity, pain, and disability (4,9,14). Suboptimal HRQoL has been observed in children with inactive disease or minimal disease activity (4).…”
Section: Introductionmentioning
confidence: 99%
“…4 6 Children with JA experience impairment in health-related QOL (HRQOL) compared to their healthy peers, as measured by decrements in the domains of physical and psychosocial well-being. 7 Chronic arthritis also negatively impacts emotional, social and school functioning. 4,5,8,9 Adult patients who had childhood-onset arthritis have been shown to have high rates of anxiety and depressive illness, 5 and have a higher mortality rate compared to the general population.…”
Section: Childhood Quality Of Life In the Changing Landscape Of Pediamentioning
confidence: 99%